Lần sau bạn chú ý ghi đầy đủ yêu cầu của đề.
Coi đây là bài toán phân tích đa thức thành nhân tử
Lời giải:
a. $x^2+x-6=x^2-2x+3x-6=x(x-2)+3(x-2)=(x-2)(x+3)$
b. $x^2+5x+6=x^2+2x+3x+6=x(x+2)+3(x+2)=(x+2)(x+3)$
c.
$x^2-4x+3=x^2-x-(3x-3)=x(x-1)-3(x-1)=(x-1)(x-3)$
d.
$x^2+5x+4=x^2+x+4x+4=x(x+1)+4(x+1)=(x+1)(x+4)$
e.
$x^2+3x-10=x^2-2x+5x-10=x(x-2)+5(x-2)=(x-2)(x+5)$
a) \(x^2+x-6=\left(x+3\right)\left(x-2\right)\)
b) \(x^2+5x+6=\left(x+2\right)\left(x+3\right)\)
c) \(x^2-4x+3=\left(x-1\right)\left(x-3\right)\)
d) \(x^2+5x+4=\left(x+4\right)\left(x+1\right)\)
e) \(x^2+3x-10=\left(x+5\right)\left(x-2\right)\)